Audit committee ownership, firm size, and audit delay: Empirical evidence from Indonesia - Wibowo, Raden Arief; Barros, Agapito; Dewi, Silfia Fitriana (IAIN Surakarta, 2022)
Research on audit committee ownership is still very limited, making it highly worthy of further investigation. Investors and regulators acknowledge the significance of having audited financial information that is released in a timely manner. Audit delay conducted by the auditor creates high information uncertainty for investors. This study aims to analyze the effect of audit committee ownership and firm size on audit delay mediated by the quality of financial reporting with a sample of 75 non-financial companies listed on the IDX in 2016-2020 with the sampling technique used is purposive sampling. This study uses path analysis with Eviews software version 9. The results of this study indicate that company share ownership and Firm Size have no effect on audit delay, financial reporting quality does not mediate the effect of company share ownership on audit delay, while financial reporting quality mediates the effect of size company against audit delay. This research contributes theoretically by enriching the literature on audit committee ownership.